‘Progress’ as a Subject and the Notion of a ‘Belief in Progress’ - Hejdánek, Ladislav (Dějiny – teorie – kritika, 2009)
The author points out a common error of historians who leave their subject and area of interest underdefined. This mistake limits the value of their often long and arduous work, and may turn it into just a collection of otherwise impressive material. Such historians then express their views on the subject proper in variously scattered notes, with no unity of purpose. In this particular case, this may be said of the vagueness of use and understanding of ‘progress’ and ‘belief in progress’ (not to mention a total absence of distinction between various meanings of ‘belief ’ and ‘faith’). The book fails to communicate the author’s point of view: Is it to be taken for granted that progress is possible or is it just a mirage, an ideological delusion?